2017
DOI: 10.1159/000485774
|View full text |Cite
|
Sign up to set email alerts
|

Response of Renal Podocytes to Excessive Hydrostatic Pressure: a Pathophysiologic Cascade in a Malignant Hypertension Model

Abstract: Background/Aims: Renal injuries induced by increased intra-glomerular pressure coincide with podocyte detachment from the glomerular basement membrane (GBM). In previous studies, it was demonstrated that mesangial cells have a crucial role in the pathogenesis of malignant hypertension. However, the exact pathophysiological cascade responsible for podocyte detachment and its relationship with mesangial cells has not been fully elucidated yet and this was the aim of the current study. Methods: Rat renal mesangia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…9 Diclofenac-induced AKI may be related to the ischemia caused by inhibition of prostaglandins synthesis in renal arterioles. 10 Diclofenac induces oxidative stress in the body and became the main cause of nephrotoxicity and AKI leading to the acceleration of lipid peroxidation and reduction of endogenous antioxidant capacity. 11 On contrary, a previous study illustrated that inhibition of COX may not be the main mechanism of diclofenac-induced AKI, which observed that redox signalling and oxidative stress as the main contributing factors in diclofenac-induced AKI.…”
Section: Introductionmentioning
confidence: 99%
“…9 Diclofenac-induced AKI may be related to the ischemia caused by inhibition of prostaglandins synthesis in renal arterioles. 10 Diclofenac induces oxidative stress in the body and became the main cause of nephrotoxicity and AKI leading to the acceleration of lipid peroxidation and reduction of endogenous antioxidant capacity. 11 On contrary, a previous study illustrated that inhibition of COX may not be the main mechanism of diclofenac-induced AKI, which observed that redox signalling and oxidative stress as the main contributing factors in diclofenac-induced AKI.…”
Section: Introductionmentioning
confidence: 99%
“…Podocyte dysfunction or injury induced by various stresses and pathological stimuli is thought to be critical for the pathogenesis of proteinuria and glomerular diseases [12, 13]. Podocytes are highly specialized and terminally differentiated visceral epithelial cells with a very limited ability to regenerate [14, 15]. Therefore, protecting them from injury and limiting their loss are important for the treatment of CKD.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it was through the kidney biopsy that we confirmed hypertensive nephropathy in the present case. Endothelial cell injury is thought to be related to kidney injury, via an increase in apoptosis and the detachment of non-viable podocytes, as angiotensin II production has been reported to increase in adjunct mesangial cells (14). Although such kidney injury occasionally requires dialysis, as in our case, the reduction in the kidney function may be reversed by long-term blood pressure control.…”
Section: Discussionmentioning
confidence: 99%